Estimation of vertical distance of incisive papilla with maxillary central incisor and their correlation in various arch form - Sapkota, Srijana Mishra; Singh, Shailendra Kumar; Thakur, Smriti Narayan; Khanal, Bibek; Pandey, Basu Raj (Journal of Chitwan Medical College, 2021)
Background: The relation of incisive papilla to the incisal edges of the maxillary central incisors in a vertical dimension could serve as a guide for inciso-cervical placement of anterior teeth in denture base according to the arch form of the edentulous patient. The aim of this study was to determine the vertical distance between incisive papilla and maxillary central incisor in different arch form. Methods: A cross-sectional study was conducted among 100 dentulous subjects. The vertical distance between the incisal edges of maxillary central incisor and center of incisive papilla was measured by a digital caliper on casts obtained from dentate subjects meeting inclusion criteria after which statistical analysis of data using SPSS v26 version. Results: The mean vertical distance between maxillary central incisor and incisive papilla were 5.97±1.03mm in ovoid, 6.09±0.98mm in square and 6.23±0.89mm in taper arch form. Conclusions: The result obtained in this study can be used as a clinical guideline for the fabrication of maxillary occlusal rim and may aid in determining the position of occlusal plane along with the reference of other anatomical landmarks.